Preface: Special Issue—College Experiences for Students with Autism Spectrum Disorder - Jackson, Scott L. J.; Hart, Logan; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Keywords: dept.aa; dept.sed

Microplastic abundances in a mussel bed and ingestion by the ribbed marsh mussel Geukensia demissa. - Khan, Matthew B; Prezant, Robert S (Marine Pollution Bulletin, 2018)
Human activities have generated large quantities of microplastics that can be consumed by filter-feeding organisms as potential food sources. As a result, organisms may experience marked reductions in growth and/or health. To date there has been no investigations connecting microplastics (MPs) with the critically important ribbed mussel Geukensia demissa. Here we examined MP abundances within a bed of G. demissa in New Jersey. Results indicate that MP densities ranged between 11,000-50,000pieces/m2. The abundance of larger MPs (5mm>=1mm) did not vary among sampling sites while the smaller MPs (<1mm) abundances did vary between sampling sites. These smaller MPs also accounted for 79% of MPs recovered from these sites. Based on the higher abundance of smaller MPs, we also investigated MP ingestion/rejection in a laboratory setting. These results confirmed that ribbed mussels can ingest MPs with negative consequences for the buoyancy of plastics rejected in feces and pseudofeces. Copyright © 2018 The Authors. Published by Elsevier Ltd.. All rights reserved.
Keywords: *Bivalvia; *Plastics/an [Analysis]; *Waste Products/an [Analysis]; *Water Pollutants, Chemical/an [Analysis]; Animals; Article; Bivalvia; Contamination; Eating; Filter-feeding organisms; Geukensia demissa; Human activities; Humans; Ingestion; Ingestion (engines); Marine pollution; Microplastic; Microplastics; Molluscs; Mussel bed; New Jersey; Plastics; Sampling site; United States; Waste Products; Water Pollutants, Chemical; abundance; analysis; animal; animal experiment; animal tissue; bivalve; body fluids and secretions; controlled study; dept.aa; eating; feces; filter feeder; growth; human; human activities; ingestion; ingestion rate; marine pollution; marsh; microplastic; mussel; nonhuman; peer-reviewed; plastic; pseudofeces; sampling; unclassified drug; waste; water pollutant

Brief report: Self-reported academic, social, and mental health experiences of post-secondary students with autism spectrum disorder - Jackson, Scott L. J.; Hart, Logan; Brown, Jane Thierfeld; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Keywords: dept.aa; dept.sed